2022
DOI: 10.1126/sciadv.abm7825
|View full text |Cite
|
Sign up to set email alerts
|

Sexually divergent development of depression-related brain networks during healthy human adolescence

Abstract: Sexual differences in human brain development could be relevant to sex differences in the incidence of depression during adolescence. We tested for sex differences in parameters of normative brain network development using fMRI data on N = 298 healthy adolescents, aged 14 to 26 years, each scanned one to three times. Sexually divergent development of functional connectivity was located in the default mode network, limbic cortex, and subcortical nuclei. Females had a more “disruptive” pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 110 publications
1
10
0
Order By: Relevance
“…However, there are relatively few studies on sex differences in adolescent MDD. A recent study demonstrated sexually divergent development of MDD-related networks (the default mode network and limbic cortex) during healthy adolescence ( 22 ). Additionally, Whittle et al reported that depression was correlated with increased amygdala growth in girls but decreased growth in boys in a longitudinal study of adolescent depression, and depressive symptoms were also correlated with reduced volume of nucleus accumbens only in girls ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are relatively few studies on sex differences in adolescent MDD. A recent study demonstrated sexually divergent development of MDD-related networks (the default mode network and limbic cortex) during healthy adolescence ( 22 ). Additionally, Whittle et al reported that depression was correlated with increased amygdala growth in girls but decreased growth in boys in a longitudinal study of adolescent depression, and depressive symptoms were also correlated with reduced volume of nucleus accumbens only in girls ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, amygdalar volumes in healthy adolescents also showed sex divergence ( 21 ); the left amygdala was smaller in girls than in boys. Dorfschmidt et al studied 298 healthy adolescents with fMRI and found sexually divergent development of brain networks within the default mode network and limbic cortex ( 22 ). Another fMRI study also demonstrated sex differences in cerebellum activation during an affective go/no-go task in depressed adolescents ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in females, we identified gene networks associated with the expression of change in appetite/weight (Darkorange) and low self-esteem (Purple) in the aINS, psychomotor agitation/retardation (Saddlebrown) in the dlPFC and difficulty in concentration/indecision (Palevioletred3) in the vmPFC that could also associate with changes in the activity of each of these brain regions. It is likely that changes in these sex-specific gene networks underly symptom expression in males or females by interfering with the activity of brain networks, as was recently shown for a cortical-subcortical circuit during adolescent development 64 . Thus, we hypothesize that the reorganization of precise transcriptional structures across brain regions in males and females may underly the expression of distinct clinical features of MDD in a sex-specific fashion.…”
Section: Discussionmentioning
confidence: 90%
“…To examine the variability of each gene's weighting coefficient, we used a bootstrapping method (resampling with replacement of the 152 cortical regions) in the PLS analysis. The ratio of the observed weight coefficient of each gene to its bootstrap standard error was used to calculate the Z-scores of each gene weight on PLS1 [17,18,33,[38][39][40].…”
Section: Transcriptional Correlates Of Case-control Regional Msnmentioning
confidence: 99%